High-strength brake pad friction material and preparation method thereof

By using copper powder matrix, hard friction components, iron powder, graphite powder and metal bonding components in the brake pad friction materials, coated iron chromium powder and copper-plated silica powder are prepared to form a reinforced friction filling structure, solving the problem of large wear of existing friction materials and achieving high strength and good wear resistance.

CN119501059APending Publication Date: 2025-02-25JIANGSU FANGYI AUTOPART MANUFACTURE CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411388158.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-08
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

In the process of increasing the friction coefficient, existing friction materials can easily lead to large wear and tear, making it difficult to maintain good wear resistance and long-term braking performance.

Method used

A high-strength brake pad friction material is used, and its composition includes a copper powder matrix, a hard friction component, iron powder, graphite powder and metal bonding component. The coated iron chromium powder and copper-plated silica powder are prepared through specific proportions and treatment methods to form a reinforced friction filling structure.

Benefits of technology

The matrix strength and wear resistance of friction materials are improved, the overall strength is enhanced, and good wear resistance and long-term braking performance are achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of friction materials, in particular to a high-strength brake pad friction material and a preparation method thereof.The friction material comprises, by mass, 65 parts of a copper powder matrix, 15-20 parts of a hard friction component, 10-15 parts of iron powder, 8-10 parts of graphite powder and 4-8 parts of a metal bonding component; according to the high-strength brake pad friction material and the preparation method thereof, the film-coated ferrochrome powder and the copper-plated silicon dioxide powder are creatively prepared to serve as friction components, and the matrix strength and wear resistance of the friction material can be improved; and due to the arrangement of the iron powder, the metal bonding component can generate an iron aluminide substance with relatively good strength to form a filling structure, so that the overall strength of the friction material is further improved, and relatively good wear resistance can be obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of friction materials, and in particular to a high-strength brake pad friction material and a preparation method thereof. Background Art

[0002] Friction materials are functional materials used in many sports machinery and equipment for transmission, steering, braking, deceleration, parking and other functions. Taking brake pad friction materials as an example, the quality of their performance directly affects the safety of braking.

[0003] Mainstream friction materials are mostly asbestos-free friction materials, including powder metallurgy friction materials with the advantages of wear resistance and less pollution. The preparation of metal-based composite materials by powder metallurgy refers to the preparation of several metal powders or metal powders and non-metallic powders in different proportions, and then uniformly mixing, pressing, sintering and post-processing to make the required shape and size. It is widely used.

[0004] At present, copper-based powder metallurgy friction materials are mostly used to maintain good heat dissipation performance and alleviate the problem of thermal bonding in the pair. However, friction materials are limited by the reason of increasing the friction coefficient. The high friction coefficient easily leads to a large amount of wear. Therefore, it is necessary to consider maintaining good friction performance while obtaining better wear resistance, so as to obtain long-term braking performance. In view of this, we propose a high-strength brake pad friction material and a preparation method thereof. Summary of the invention

[0005] The purpose of the present invention is to solve the deficiencies mentioned in the above background technology and to provide a high-strength brake pad friction material and a preparation method thereof.

[0006] In order to solve the above technical problems, the present invention adopts the following technical solutions: A high-strength brake pad friction material, the mass fractions of the components of the friction material include: Copper powder matrix: 65 parts; Hard friction component: 15-20 parts; Iron powder: 10-15 parts; Graphite powder: 8-10 parts; Metal bonding component: 4-8 parts.

[0007] Preferably, the copper powder matrix is ​​one of 200-300 mesh alumina copper powder, electrolytic copper powder and atomized copper powder.

[0008] Preferably, the hard friction component comprises coated ferrochrome powder and copper-plated silica powder in a mass ratio of 1:1-1.6.

[0009] Preferably, the metal bonding component comprises tin powder and aluminum powder with a particle size of 200-600 mesh and a mass ratio of 1:0.5-1.

[0010] Preferably, the raw materials for preparing the coated ferrochrome powder are molybdenum disulfide spray and 300-400 mesh high chromium cast iron powder. The specific preparation method is: use molybdenum disulfide spray to spray the dried high chromium cast iron powder for use, repeatedly spread it until the high chromium cast iron powder is evenly moistened, dry it at 60-80°C, and take the powder with a particle size of 200-300 mesh as the coated ferrochrome powder for use.

[0011] Preferably, the preparation method of the copper-plated silica powder comprises the following specific steps: Step 1: Pre-treat 300-400 mesh silica powder by first washing it with distilled water, then sequentially washing it with acetone and 5-10wt% hydrochloric acid solution by soaking and stirring for 1-2h, and finally washing it with distilled water again and drying it for later use; Step 2: Sensitization and activation treatment: first, use the sensitizing solution to stir and mix at room temperature for 15-30 minutes, and then use the activating solution to stir and mix at room temperature for 15-30 minutes; Step 3: Copper plating, prepare chemical copper plating solution, and treat at 40°C for 10-20 minutes; Step 4: Post-treatment, the product of step 3 is placed in an ethanol solution and stirred for 0.5-1h, then washed again with the ethanol solution and placed in a vacuum drying oven for drying to obtain copper-plated silica powder for use.

[0012] Preferably, the sensitizing solution comprises 20 g / L of stannous chloride dihydrate and 40 ml / L of hydrochloric acid.

[0013] Preferably, the activation solution comprises 0.25 g / L palladium chloride and 2.5 ml / L hydrochloric acid.

[0014] Preferably, the chemical copper plating solution includes 25 g / L of disodium ethylenediaminetetraacetate, 14 ml / L of formaldehyde, 16 g / L of copper sulfate pentahydrate, 20 g / L of potassium sodium tartrate, and 20 g / L of sodium hydroxide.

[0015] A method for preparing a high-strength brake pad friction material, the specific steps of the preparation method are: Step 1: Weigh each raw material component in proportion, mix at 400-600r / min for 1-2h; Step 2: Pre-pressing, applying pressure of 350-500MPa at room temperature and maintaining pressure for 0.5-1min; Step 3: hot pressing and sintering, sending the molded part into a vacuum furnace, controlling the sintering temperature to 850-1000°C; the sintering pressure to 5-25Mpa, maintaining the pressure and heat preservation for 0.5-1h, and then cooling to room temperature to obtain a high-strength friction material.

[0016] Compared with the prior art, the present invention has the following beneficial effects: The high-strength brake pad friction material and preparation method thereof creatively prepares coated ferrochrome powder and copper-plated silica powder as friction components, which can improve the matrix strength and wear resistance of the friction material; iron powder and metal bonding components are provided to produce aluminized iron materials with relatively good strength to form a filling structure, thereby further improving the overall strength of the friction material and achieving relatively good wear resistance. DETAILED DESCRIPTION

[0017] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. In the absence of conflict, the embodiments in this application and the features in the embodiments can be combined with each other. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work belong to the scope of protection of the present invention.

[0018] The present invention describes the above technical solution in detail through the following embodiments: Example 1

[0019] A high-strength brake pad friction material, the mass fractions of each component of the friction material include: 300 mesh electrolytic copper powder: 65 parts; Coated ferrochrome powder: 10 parts; Copper-plated silica powder: 10 parts; 325 mesh iron powder: 10 parts; 195 type flake graphite: 8-10 parts; 325 mesh tin powder: 4 parts; 325 mesh aluminum powder: 4 parts.

[0020] It should be noted that the raw materials for preparing the coated ferrochrome powder in this embodiment are Senya SY-97 molybdenum disulfide spray and 400-mesh high-chromium cast iron powder sold by Nangong Ruiteng Alloy Materials Co., Ltd. The specific preparation method is: use molybdenum disulfide spray to spray the dried high-chromium cast iron powder for use, spray the molybdenum disulfide spray that accounts for 30% of the mass of the high-chromium cast iron powder, repeatedly spread until the high-chromium cast iron powder is evenly moistened, dry at 80°C, and take the powder with a particle size between 200-300 mesh as the coated ferrochrome powder for use; in addition, electrolytic copper powder was purchased from Suzhou Futian High-tech Powder Co., Ltd. CE-5 type 300-mesh powder, graphite was purchased from China Graphite Group Co., Ltd. 195 type flake graphite; 325 mesh iron powder, 325 mesh tin powder, and 325 mesh aluminum powder were all purchased from Beijing Yi Jin New Materials Technology Co., Ltd.

[0021] Silicon dioxide and ferrochrome powder are the main friction fillers, and they need to be mixed evenly during the mixing process to avoid uneven distribution problems such as segregation, which is beneficial to improving the uniformity of dispersion. Therefore, in this embodiment, they are copper plated and coated respectively.

[0022] The specific steps of the preparation method of copper-plated silica powder in this embodiment are as follows: Step 1: Pre-treat 400-mesh silica powder by first washing it with distilled water, then sequentially washing it with acetone and 6wt% hydrochloric acid solution by immersion and stirring for 1 hour, and finally washing it with distilled water again and drying it for later use; Step 2: Sensitization and activation treatment, first use a sensitizing solution to stir and mix at room temperature for 20 minutes, then use an activating solution to stir and mix at room temperature for 20 minutes, wherein the sensitizing solution includes 20 g / L of stannous chloride dihydrate and 40 ml / L of hydrochloric acid, and the activating solution includes 0.25 g / L of palladium chloride and 2.5 ml / L of hydrochloric acid; Step 3: Copper plating, preparing a chemical copper plating solution, the chemical copper plating solution includes 25g / L disodium ethylenediaminetetraacetic acid, 14ml / L formaldehyde, 16g / L copper sulfate pentahydrate, 20g / L potassium sodium tartrate, and 20g / L sodium hydroxide, and treating at 40°C for 15min; Step 4: Post-treatment, the product of step 3 is placed in an ethanol solution and stirred for 1 hour, then washed again with the ethanol solution and placed in a vacuum drying oven for drying to obtain copper-plated silica powder for use.

[0023] Finally, the preparation method of the high-strength brake pad friction material in this embodiment, the specific steps of the preparation method are: Step 1: Weigh each raw material component according to the proportion, mix at 500r / min for 2h; Step 2: Pre-pressing, applying 500MPa pressure at room temperature and maintaining pressure for 1min; Step 3: hot pressing and sintering, sending the molded part into a vacuum furnace, controlling the sintering temperature to 950°C; the sintering pressure is 18Mpa, and after sintering for 1 hour under pressure and heat preservation, cooling to room temperature to obtain a high-strength friction material.

[0024] The role of tin powder, aluminum powder and iron powder in the embodiment is not limited to a simple reinforcing filler. The copper-based friction material has a high-temperature hot pressing sintering step. Tin powder, aluminum powder and iron powder can be hot-melted to act as a binder, which is beneficial to strengthen and improve the overall curing strength.

[0025] At the same time, considering that high-temperature braking is prone to wear in the later stage, the tin powder is used as a low-melting-point hot-melt bonding component. In addition, the iron powder will combine with the aluminum powder under high-temperature sintering conditions to generate a harder aluminum-iron material, which has high strength and high temperature resistance, and can avoid the problem of thermal decay caused by softening of the friction material matrix under high-temperature braking conditions; and based on physical properties, high hardness is beneficial to improving the wear resistance of the friction material; it is worth noting that the coated ferrochrome powder in the present application provides a structure combining molybdenum disulfide and ferrochrome powder. Molybdenum disulfide is a lubricant that can form a stable lubricating film at the friction interface when friction occurs, realizing the combination of lubricating phase and friction component, and then improving the wear resistance of the material. At the same time, when molybdenum disulfide is around the friction particles, it can effectively reduce the problem of hard scratches on the dual material caused by friction particles, which is beneficial to extending the service life of the dual parts.

[0026] In this embodiment, the surface of the silica powder is copper-plated, and the silica powder and the electrolytic copper powder can be tightly bonded through the copper-plated layer. The connection strength is much greater than that of the molding method through physical hot pressing, because the copper-plating process eliminates the surface stress of the silica powder, which is beneficial to reduce the pores between the silica powder and the electrolytic copper powder caused by the stress, thereby improving the strength of the material.

[0027] Example 2

[0028] The difference between this embodiment and embodiment 1 is that the hard friction component in this embodiment specifically includes coated ferrochrome powder and copper-plated silica powder in a ratio of 1:1.5, that is, 8 parts of coated ferrochrome powder and 12 parts of copper-plated silica powder, and other conditions are the same; Example 3

[0029] The difference between this embodiment and embodiment 1 is that the hard friction component in this embodiment specifically includes coated ferrochrome powder and copper-plated silica powder in a ratio of 1:0.6, that is, 12.5 parts of coated ferrochrome powder and 7.5 parts of copper-plated silica powder, and other conditions are the same; Example 4

[0030] The difference between this embodiment and embodiment 1 is that: in this embodiment, only 2 portions of aluminum powder are provided, and other conditions are the same; Comparative Example 1

[0031] The difference between this comparative example and Example 1 is that: in this comparative example, no aluminum powder and iron powder are provided, and other conditions are the same; Comparative Example 2

[0032] The difference between this comparative example and Example 1 is that: in this comparative example, no coated ferrochrome powder is provided, and other conditions are the same; Comparative Example 3

[0033] The difference between this comparative example and Example 1 is that: in this comparative example, copper-plated silica powder is not provided, and other conditions are the same; Comparative Example 4

[0034] The difference between this comparative example and Example 1 is that only high chromium cast iron powder and silicon dioxide powder are provided in this comparative example, and no coating or copper plating treatment is performed on the surface thereof, and other conditions are the same; Samples were prepared according to the above-mentioned Examples 1 to 4 and Comparative Examples 1 to 4, and their material properties, friction coefficients and wear amounts were tested. The specific testing methods were as follows: (1) Material properties: Test the Brinell hardness. Use the HB-3000B Brinell hardness tester to measure the Brinell hardness of the friction material. (2) Friction coefficient: MMW-1A universal friction and wear testing machine was used. Before the test, the surface of the test block was polished to ensure that the material surface was smooth and flat. The pressure load was 30N, the speed was 200r / min, and the friction time was 10min. The small thrust ring specimen was made of 32GrMn steel, with a dual diameter of 28mm. The average value was taken after 5 measurements. (3) Wear amount: measured by the mass loss of the test block per unit time. The turntable speed is 330 r / min, and the test piece is worn on the turntable for 180 min. The wear amount is weighed and tested as a percentage of the original mass.

[0035] The specific data is as follows:

[0036] From the data analysis in the above table, it can be seen that: in Example 2, the proportion of coated ferrochrome powder decreased, and although the Brinell hardness and wear amount were similar, the friction coefficient decreased slightly; in Example 3, the excessive amount of coated ferrochrome powder and a small amount of copper-plated silica powder caused a significant decrease in Brinell hardness and wear performance, although the friction coefficient was significantly improved. Considering that the coated ferrochrome powder is the main friction component, and the copper-plated silica powder affects the overall performance of the friction material matrix, when the copper-plated silica powder is too little, it is not conducive to hot pressing molding, and the ratio of the two needs to be controlled; and in Example 4, the reduction of aluminum powder content, from the data, shows that the performance of hardness, friction coefficient and wear amount are all reduced. Considering that the aluminum powder needs to be appropriate to produce aluminum iron material, and then obtain the corresponding mechanical properties; In addition, the absence of aluminum powder and iron powder in Comparative Example 1 resulted in a significant decrease in the hardness, friction coefficient and wear loss. Considering that the aluminum powder and iron powder have reaction products, the overall performance of the friction material can be improved. They are not simple friction fillers and will not cause such a large performance degradation. Referring to the data of Comparative Example 2, if the coated ferrochrome powder is not used, its hardness and friction coefficient decrease, and the wear amount decreases, but its wear is related to the friction coefficient. As a friction material, its friction coefficient is important, so the coated ferrochrome powder as a friction component cannot be missing; the Brinell hardness and wear amount in Comparative Example 3 are not good. Considering that the copper-plated silica powder is also a filler, its strength is reduced and the friction coefficient remains unchanged, the material itself is more likely to cause wear; It can be clearly seen from Comparative Example 4 that the lubricity of the high chromium cast iron powder without coating is reduced, which brings the advantage of a slight increase in the friction coefficient, but the silicon dioxide powder without copper plating causes the attenuation of the overall strength of the friction material, ultimately resulting in a major defect of large wear; In summary, maintaining the friction coefficient while having good material mechanical properties is a necessary condition for reducing wear. The presence of iron powder and aluminum powder can further enhance the Brinell hardness and friction coefficient, overcoming or compensating for the problem of partial friction coefficient attenuation caused by molybdenum disulfide film lubrication.

[0037] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

Claims

1. A high-strength brake pad friction material, characterized in that: The mass fractions of the components of the friction material include: Copper powder matrix: 65 parts; Hard friction component: 15-20 parts; Iron powder: 10-15 parts; Graphite powder: 8-10 parts; Metal bonding component: 4-8 parts.

2. The high-strength brake pad friction material according to claim 1, characterized in that: The copper powder matrix is ​​one of 200-300 mesh alumina copper powder, electrolytic copper powder and atomized copper powder.

3. The high-strength brake pad friction material according to claim 1, characterized in that: The hard friction component comprises coated ferrochrome powder and copper-plated silicon dioxide powder in a mass ratio of 1:1-1.

6.

4. The high-strength brake pad friction material according to claim 1, characterized in that: The metal bonding component comprises tin powder and aluminum powder with a particle size of 200-600 meshes and a mass ratio of 1:0.5-1.

5. The high-strength brake pad friction material according to claim 3, characterized in that: The raw materials for preparing the coated ferrochrome powder are molybdenum disulfide spray and 300-400 mesh high chromium cast iron powder. The specific preparation method is: use molybdenum disulfide spray to spray the dried high chromium cast iron powder for use, repeatedly spread until the high chromium cast iron powder is evenly moistened, dry at 60-80°C, and take powder with a particle size of 200-300 mesh as the coated ferrochrome powder for use.

6. The high-strength brake pad friction material according to claim 3, characterized in that: The specific steps of the preparation method of the copper-plated silica powder are: Step 1: Pre-treat 300-400 mesh silica powder by first washing it with distilled water, then sequentially washing it with acetone and 5-10wt% hydrochloric acid solution by soaking and stirring for 1-2h, and finally washing it with distilled water again and drying it for later use; Step 2: Sensitization and activation treatment: first, use the sensitizing solution to stir and mix at room temperature for 15-30 minutes, and then use the activating solution to stir and mix at room temperature for 15-30 minutes; Step 3: Copper plating, prepare chemical copper plating solution, and treat at 40°C for 10-20 minutes; Step 4: Post-treatment, the product of step 3 is placed in an ethanol solution and stirred for 0.5-1h, then washed again with the ethanol solution and placed in a vacuum drying oven for drying to obtain copper-plated silica powder for use.

7. The high-strength brake pad friction material according to claim 6, characterized in that: The sensitizing solution includes 20 g / L of stannous chloride dihydrate and 40 ml / L of hydrochloric acid.

8. The high-strength brake pad friction material according to claim 6, characterized in that: The activation solution includes 0.25 g / L of palladium chloride and 2.5 ml / L of hydrochloric acid.

9. The high-strength brake pad friction material according to claim 6, characterized in that: The chemical copper plating solution includes 25 g / L of disodium ethylenediaminetetraacetate, 14 ml / L of formaldehyde, 16 g / L of copper sulfate pentahydrate, 20 g / L of potassium sodium tartrate, and 20 g / L of sodium hydroxide.

10. A method for preparing a high-strength brake pad friction material, applicable to the high-strength brake pad friction material according to any one of claims 1 to 9, characterized in that: The specific steps of the preparation method are: Step 1: Weigh each raw material component according to the proportion, mix at 400-600r / min for 1-2h; Step 2: Pre-pressing, applying pressure of 350-500MPa at room temperature and maintaining pressure for 0.5-1min; Step 3: hot pressing and sintering, sending the molded part into a vacuum furnace, controlling the sintering temperature to 850-1000°C; the sintering pressure to 5-25Mpa, maintaining the pressure and heat preservation for 0.5-1h, and then cooling to room temperature to obtain a high-strength friction material.